REVITALIZING CEREAL CROP PRODUCTION: A CRITICAL REVIEW OF THE EFFECTS OF MACRO AND MICRO-NUTRIENT FOLIAR SPRAYS ON GROWTH AND YIELD - AHMED, MI; IRUM, A; KHAN, AA; NOOR, S; NAZ, A; AHMAD, F; GHAFOOR, S; SAJJAD, S; KAUSAR, R; NAWAZ, S; et al. (Biological and Clinical Sciences Research Journal, 2024)
Foliar fertilizer treatment has been identified as a viable source for boosting cereal crop growth and productivity. However, some elements such as application method, nutrient supply, and timing must be taken into account to get the best results. Foliar spray is an effective and focused method of nutrient delivery since it avoids soil shortages and encourages direct absorption through leaves. This review emphasizes the significance of macronutrients for crop growth and development, including nitrogen, phosphorus, potassium, etc. It also looks at how micronutrients like zinc, iron, manganese, etc affect the quantity and quality of agricultural production. Foliar spraying can be a useful method of giving these nutrients to crops, especially during crucial growth stages. To reduce the possibility of causing harm to the crops and surrounding environment, safety precautions should be taken throughout the foliar spraying process. These safety measures include careful nozzle selection, equipment calibration, and cleaning. Overall, the application of foliar nutrients has the potential to result in the production of cereal crops that are more effective and sustainable.